2020
DOI: 10.1016/j.eats.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of a Coracoid Fracture Associated With Acromioclavicular Dislocation: Technical Note

Abstract: Operative management of a coracoid process fracture is indicated in case of painful nonunion, displacement of more than 1 cm, or multiple disruptions of the superior shoulder suspensory complex. Several techniques have been described with open reduction of the fracture and internal fixation using cortical screws with or without additional fixation of the acromioclavicular joint. This Technical Note aims to introduce an alternative safe, minimally invasive method for arthroscopic fixation of a coracoid fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“… 22 If CP fracture occurs with an AC-joint dislocation, it is possible to address CP alone or with fixation of the AC joint. 6 All our cases had a double disruption of the SSSC. The CP can be stabilized with cannulated screws.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“… 22 If CP fracture occurs with an AC-joint dislocation, it is possible to address CP alone or with fixation of the AC joint. 6 All our cases had a double disruption of the SSSC. The CP can be stabilized with cannulated screws.…”
Section: Discussionmentioning
confidence: 66%
“…Multiple disruptions may cause nonunion due to shoulder girdle instability. 6 Literature pertaining to these injuries and their management guidelines is lacking. A review by Kose et al 5 of 48 cases (1946–2018) found a variety of treatment options ranging from conservative management to complex surgical reconstruction and fixation.…”
Section: Introductionmentioning
confidence: 99%
“…This article demonstrates an arthroscopy-aided approach to fixing coracoid fractures. Passaplan et al 8 described an arthroscopic assisted technique for a type II fracture with simultaneous reduction of the acromioclavicular joint. The technique they describe demonstrates reduction of the base of the coracoid back to the glenoid, whereas our technique demonstrates how to arthroscopically fix a fracture distal to the CC ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there is only a single report of arthroscopic fixation of an Ogawa type I fracture and no reported cases of arthroscopic fixation of an Ogawa type II fracture. 8 This case will highlight the first reported use of arthroscopy to debride a Type II coracoid nonunion, as well as the use of arthroscopic assisted percutaneous fixation of a Type II coracoid fracture.…”
mentioning
confidence: 93%
“…In 2020, Passaplan et al . describe an arthroscopic screw fixation technique [ 12 ]. The procedure is technically demanding but, it permits a very good visualization of the fracture for reduction and fixation, whereas visualization of the coracoid process remains difficult even in open procedures.…”
Section: Discussionmentioning
confidence: 99%